A survey of root canal treatment of molar teeth by general dental practitioners in private practice in Saudi Arabia - Khalid S. Al-Fouzan (Elsevier, 2010)
The purpose of this study was to evaluate the practice and depth of knowledge of root canal treatment by general dental practitioners working in private dental centers in different cities within the Kingdom of Saudi Arabia. A questionnaire was distributed to 400 general dental practitioners. Completed questionnaires were analyzed in term of simple summary statistics. A total of 252 (63%) practitioners responded. The majority of the respondents were Syrians (59%) and Egyptians (32%). Ninety-one per cent of the respondents indicated that they performed root canal treatment. Amongst those who carried out root canal treatment, only seven practitioners (3%) used rubber dam for isolation. More than half of the respondents (55%) used saline to irrigate canals during treatment. Forty-six per cent of practitioners used formocresol as an inter appointment medicament. The standardized and step-back preparation techniques were the method of choice for the majority of the respondents (91%). Ninety-seven per cent of the practitioners used stainless steel hand instruments to prepare root canals and the majority (92%) used gutta-percha for obturation. Seventy-four per cent of the respondent used cold lateral condensation. The average number of radiographs routinely taken for root canal treatment was four. Ninety-three per cent indicated that they usually completed a root canal treatment of molar teeth in three or more visits. Eighty-eight per cent of the practitioners preferred waiting for 1 or 2 weeks to restore the teeth permanently. Results of this study confirm that many general dental practitioners are not following quality guidelines for endodontic treatment. Keywords: Root canal treatment, Private practice, Saudi Arabia